A derivative of butyric acid, the fermentation metabolite of staphylococcus epidermidis, inhibits the growth of a staphylococcus aureus strain isolated from atopic dermatitis patients - Traisaeng, S. (MDPI AG, 2021)
10.3390/toxins11060311